2021
DOI: 10.1002/cjp2.230
|View full text |Cite
|
Sign up to set email alerts
|

STING pathway expression in low‐grade serous carcinoma of the ovary: an unexpected therapeutic opportunity?

Abstract: Ovarian carcinoma histotypes are distinct diseases with variable clinical outcomes and response to treatment. There is a need for new subtype-specific treatment modalities, especially for women with widespread and chemo-resistant disease. Stimulator of interferon genes (STING) is a part of the cGAS-STING pathway that mediates innate immune defence against infectious DNA-containing pathogens and also detects tumour-derived DNA and generates intrinsic antitumour immunity. The STING signalling pathway is suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The STING pathway is suppressed through epigenetic silencing or loss of function mutations. While these data require further validation, the STING pathway could offer a prospect of therapeutic intervention [ 102 ].…”
Section: Conclusion/future Directionsmentioning
confidence: 99%
“…The STING pathway is suppressed through epigenetic silencing or loss of function mutations. While these data require further validation, the STING pathway could offer a prospect of therapeutic intervention [ 102 ].…”
Section: Conclusion/future Directionsmentioning
confidence: 99%
“…In contrast, endometrioid tumors were indicated to have a stronger presence of Tregs (FOXP3 and CTLA-4), and tumor PD-L1 and IDO1 levels on par with HGSC. Interestingly, LGSC had high levels of STING, an immune stimulatory target which has been suggested an attractive therapeutic target in OC in general 32 , and has previously been shown to be highly expressed in LGSC in particular 33 . The small set of four clear cell tumors showed an overall weak immune response relative the other histotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In OC, the expressional pattern of STING has been characterized across ovarian tumor histotypes. Huvila et al (2021) reported that STING expressed highly in low grade serous ovarian carcinoma and serous borderline tumors, heterogeneously expressed in high-grade serous and endometrioid carcinomas, but with low levels in clear cell and mucinous carcinomas. Such expression pattern of STING across OC subtypes may suggest differed functions of STING in different cellular origins of OC tumorigenesis.…”
Section: Overview Of Cgas/sting Signaling Pathwaymentioning
confidence: 99%